2012
DOI: 10.1182/blood-2011-09-381905
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 is a tumor suppressor in classical Hodgkin lymphoma

Abstract: IntroductionFOXO1 belongs to the subgroup O of forkhead transcription factors (FOX), which share the highly conserved forkhead DNAbinding domain. This O subgroup consists of the 4 members, FOXO1, FOXO3, FOXO4, and FOXO6. 1 FOXO transcription factors control different cellular processes, such as stress response, proliferation, apoptosis, and cell differentiation. 2 FOXO target genes include the cell-cycle regulators CDKN1A and CDKN1B, proapoptotic genes BIM, PMAIP1/NOXA, and FASL as well as oxidative stress pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
156
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(169 citation statements)
references
References 46 publications
11
156
2
Order By: Relevance
“…62 The tumor suppressor FOXO1, which is inactivated by AKT, is repressed in HRS cells; only one of 32 cases analyzed by Xie et al was FOXO1 positive. 63 Inhibition of AKT caused a dose-dependent increase in FOXO1 expression in classic HL cell lines. 63 Together, these findings emphasize the important role of PI3K in hematologic malignancies and suggest that inhibition of this pathway may be a viable therapeutic approach.…”
Section: Mantle Cell Lymphomamentioning
confidence: 99%
See 1 more Smart Citation
“…62 The tumor suppressor FOXO1, which is inactivated by AKT, is repressed in HRS cells; only one of 32 cases analyzed by Xie et al was FOXO1 positive. 63 Inhibition of AKT caused a dose-dependent increase in FOXO1 expression in classic HL cell lines. 63 Together, these findings emphasize the important role of PI3K in hematologic malignancies and suggest that inhibition of this pathway may be a viable therapeutic approach.…”
Section: Mantle Cell Lymphomamentioning
confidence: 99%
“…63 Inhibition of AKT caused a dose-dependent increase in FOXO1 expression in classic HL cell lines. 63 Together, these findings emphasize the important role of PI3K in hematologic malignancies and suggest that inhibition of this pathway may be a viable therapeutic approach. Further investigation of PI3K inhibitors in hematologic malignancies may help to establish the role of this drug class in the treatment armamentarium and improve patient outcomes.…”
Section: Mantle Cell Lymphomamentioning
confidence: 99%
“…In view of the fact that, in our mouse model, expression of Tg myristoylated Akt1 (Akt1 Tg) in T and B cells did not lead to B-cell expansion [18] and that enhanced Akt signaling is linked to autoimmunity and generation of tumors [19,20], we assessed the effects of constitutive Akt1 signals on B-cell function and development. We found a reduced BCR-induced proliferation of splenic B cells from Akt1 Tg mice, which correlated with reduced activation of several signaling cascades.…”
Section: Introductionmentioning
confidence: 99%
“…Given the critical role for the Akt/FOXO1 axis in the regulation of cell survival (Rena et al, 1999;Xie et al, 2012), we examined the effect of miR-9 overexpression on Akt and FOXO1 phosphorylation in ovarian cancer cells. Western blot analysis showed that the phosphorylation levels of Akt and FOXO1 were significantly (p<0.05) lower in miR-9-overexpressing SKOV3 cells than in those transfected with control oligonucleotides ( Figure 4).…”
Section: Mir-9 Overexpression Inhibits Akt Activation and Foxo1 Phospmentioning
confidence: 99%
“…Phosphorylation and inactivation of forkhead box protein O1 (FOXO1) is an important mechanism by which Akt activation promotes cell survival (Rena et al, 1999). FOXO1 acts as a tumor suppressor in a variety of cancers including ovarian cancer (Goto et al, 2008;Xie et al, 2012). Several studies have demonstrated that the anticancer effect of curcumin is associated with the modulation of FOXO1 expression (Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%